A comprehensive investigation to inform effective talent development in sport - Dunn, E. L. (Bangor University, 2023)
Despite heavy investment, many talent development pathways are inefficient and at risk of talent wastage (Baker et al., 2017; MacNamara & Collins, 2011). The present thesis aimed to identify multidimensional characteristics that could inform more effective talent development in sport. The aim of Chapter 1 was to systematically review longitudinal quantitative and qualitative talent development and talent selection research to provide an understanding of current characteristics known to be important within effective talent development. Chapters 2 and 3 aimed to address the research lacunas revealed by Chapter 1 through investigation of male and female players` developmental experiences prior to, and progression through, GB Hockey`s elite development programme (EDP). Overall, the present thesis advanced the field of talent development and should help practitioners better support athletes through the creation of more effective talent development environments.